Off-shell four photon amplitudes in the worldline formalism - Lopez Lopez, Misha Arturo (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
In this thesis, we obtain the exact result for the one-loop o-shell four-photon amplitude in D dimension and with one, two and four photons in the low energy limit in both, scalar and spinor quantum electrodynamics. For this purpose, we use the techniques and methods of the worldline formalism. Furthermore, we test our results by computing a correction to the photon propagator in an external field and the two-loop β-function.

En esta tesis obtenemos el resultado exacto para la amplitud cuatro-fotón a un-lazo fuera de la capa de masa en D dimensiones y con uno, dos y cuatro fotones en el límite de bajas energías en electrodinámica cuántica escalar y espinorial. Para este propósito, usamos las técnicas y métodos del formalismo línea de mundo. Además, verificamos nuestros resultados al calcular una corrección del propagador del fotón en un campo externo y de la función-β a dos-lazos.
Instituto de Física y Matemáticas. Maestría en Ciencias en el Área de Física
Keywords: info:eu-repo/classification/cti/1; IFM-M-2018-1240; Electrodinámica cuántica; Un-lazo; Espinorial; Hipergeométrica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1248